Tailoring TiO2 nanotube‐interlaced graphite carbon nitride nanosheets for improving visible‐light‐driven photocatalytic performance - Wang, Yang (2018)
Rapid recombination of photoinduced electron–hole pairs is one of the major defects in graphitic carbon nitride (g‐C3N4)‐based photocatalysts. To address this issue, perforated ultralong TiO2 nanotube‐interlaced g‐C3N4 nanosheets (PGCN/TNTs) are prepared via a template‐based process by treating g‐C3N4 and TiO2 nanotubes polymerized hybrids in alkali solution. Shortened migration distance of charge transfer is achieved from perforated PGCN/TNTs on account of cutting redundant g‐C3N4 nanosheets, leading to subdued electron–hole recombination. When PGCN/TNTs are employed as photocatalysts for H2 generation, their in‐plane holes and high hydrophilicity accelerate cross‐plane diffusion to dramatically promote the photocatalytic reaction in kinetics and supply plentiful catalytic active centers. By having these unique features, PGCN/TNTs exhibit superb visible‐light H2‐generation activity of 1364 µmol h−1 g−1 (λ > 400 nm) and a notable quantum yield of 6.32% at 420 nm, which are much higher than that of bulk g‐C3N4 photocatalysts. This study demonstrates an ingenious design to weaken the electron recombination in g‐C3N4 for significantly enhancing its photocatalytic capability.